La ratificación de la CEDAW como hito en la lucha por los derechos de las mujeres en el Perú - Huaita Alegre, Marcela (2019)
In Peru, the ratification of “The Convention on the Elimination of all forms of Discrimination Against Women (CEDAW)” that takes place in the beginnings of the 80’s is part of a transition process not only in the political front, but also between two generations of women activists. One of which was represented by a group of professionals called to take an active role in the political front, women such as former deputy and first PUCP woman lawyer, Matilde Pérez Palacio as well as other founders of NGO’s focused on child protection and abandoned mothers, such as María Vita de Alvarez. Prestigious group of professionals linked to “Consejo Nacional de Mujeres”, founded in 1923, such as Sara Pérez Palacio, or Olga Paredes Lañas de De Olarte, just to name a few. This is the generation of women called to give a positive outlook towards the ratification of CEDAW -among which we find an important contingent of PUCP women lawyers, which they all do from their institutions by voicing the criticism about the difficult situation in which women lived then. Conversely, the next generation of women activists who represent the second wave of the Peruvian feminist movement are the ones called, years later, to claim the CEDAW. Moreover, this is the generation called to take a stand and assume now the political and public responsibility, just as the previous generation did.